The role of plasma angiotensin-converting enzyme and interleukin-6 levels on the prognosis of non-dialysis chronic kidney disease patients - Budi Susetyo Pikir; Mochamad Yusuf Alsagaff; Satriyo Dwi Suryantoro; Ifan Ali Wafa; Nando Reza Pratama; David Setyo Budi; Bayu Satria Wiratama; Citrawati Dyah Kencono Wungu (GarVal Editorial Ltda., 2023)
Context: Inflammatory factors and oxidative stress were discovered to play significant roles in the progression of chronic kidney disease (CKD). There is, however, no research on the direct impact of high plasma angiotensin converting enzyme (ACE) and interleukin (IL)-6 levels on CKD prognosis, particularly in non-hemodialysis patients. Aims: To investigate the potential role of plasma ACE and IL-6 levels in CKD prognosis. Methods: A total of 75 non-dialysis CKD patients participated in this cross-sectional study. The estimated glomerular filtration rate (e-GFR) and albuminuria were used to determine the prognosis of CKD. The plasma ACE and IL-6 levels were measured using an enzyme-linked immunoassay (ELISA). Spearman's rank correlational analysis was used to examine the relationship between ACE and IL-6 plasma levels with the prognosis of CKD. Results: The result showed a statistically significant correlation between age and plasma ACE (p = 0.038, r = 0.241), serum creatinine, and urine albumin-creatinine ratio with CKD prognosis (p<0.0001). A negative significant correlation was found between the e-GFR and CKD prognosis (p<0.0001). Additionally, there were also significant correlations between plasma ACE and IL-6 with CKD prognosis (p = 0.021, r = 0.266 and p = 0.04, r = 0.238, respectively). A significant positive correlation was also found between plasma ACE and IL-6 (p = 0.024, r = 0.260). Conclusions: There was a significant correlation between plasma ACE and IL-6 levels with CKD prognosis. Further investigation revealed a statistically significant positive relationship between plasma ACE and IL-6 levels.